Teaching Maharah Al-Kalam Through Digital Media in Higher Education - Aniqah Laili Abidah; Agung Setiyawan; M. Naufal Al Qurthuby Fuady S; Neisya Azaria Adinda Putri (Institut Agama Islam Negeri Curup, 2026)
Speaking skill (maharah al-kalam) is a crucial aspect of Arabic language learning; however, university students still face various challenges, such as the lack of a language-rich environment and teaching methods that are not contextual. This study aims to systematically examine the effectiveness of digital media in teaching maharah al-kalam to university students by integrating the Input Hypothesis and the Technology Acceptance Model (TAM) as the analytical framework. The method employed is a Systematic Literature Review (SLR) following the PRISMA procedure. A total of 197 records were initially identified from Google Scholar, ERIC, and ResearchGate. After screening and eligibility assessment based on predetermined inclusion criteria, 26 scholarly articles published between 2020 and 2025 were included in the final review. The findings indicate that, from the perspective of the Input Hypothesis, digital media platforms such as YouTube, TikTok, Vlogs, Plotagon, and WhatsApp provide comprehensible input that supports students’ speaking development. From the perspective of the Technology Acceptance Model (TAM), these media are effective because they are perceived as useful and easy to use, which encourages active participation and increases students’ self-confidence. These findings show that digital media function not only as sources of language input but also as accessible and acceptable learning tools for teaching maharah al-kalam in higher education. Nevertheless, challenges such as limited internet access, technical difficulties, and psychological barriers continue to hinder its implementation. This study recommends the strategic integration of digital media into the Arabic language learning curriculum and the development of hybrid learning models that are more responsive to students' needs in the digital era.